ÐÑƒÑ‚Ð¾Ð±Ð°Ð½ÐºÐ¸ Ð¿ÑƒÐ¿Ð¾Ð²Ð¸Ð½Ð½Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸: Ð¼ÐµÑ‚Ð¾Ð´Ñ‹ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð¸ Ñ‚ÐµÑÑ‚Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Babijchuk, L. A.; Kudokotseva, O. V.; Zubov, P. M.; Ryazantsev, V. V.; Zubova, O. L.; Gurina, T. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There was developed the technology of the cord blood nucleated cell cryopreservation which allowed to reduce DMSO concentration till 5% and provide the high recovery and structural and functional integrity of the mononuclear cell fraction in the preparation including the hemopoietic CD34+-stem cells.